EDUKASI POLA HIDUP BERSIH DAN SEHAT SERTA PENERAPAN ADAPTASI KEBIASAAN BARU PASCA PANDEMI COVID19 - Al Sukri, Saipul; Zulfahmi, Zulfahmi; Ridha, Irfan; Ilosa, Abdiana; Zulhaida, Zulhaida; Hayani, Nurrahmi; Rahmadeni, Rahmadeni; Darni, Darni; Wahyudi, Hakmi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
E-Warong Berkah Harapan is one of the places where the SEMBAKO program aid packages are distributed, which serves nearly 400 aid recipients every month. The crowd that occurred was not impossible to cause a new transmission clutser for Covid19. Therefore, the service team from UIN Sultan Syarif Kasim conducted counseling on "Education on Healthy Lifestyle and the application of Adaptation to New Life Habits Post-Covid19 Pandemic". Before the counseling was carried out, the SEMBAKO package distribution activities neglected to maintain a minimum distance of 1 meter, did not use a mask and did not yet provide adequate hand washing facilities. The pre-test results about the management's knowledge also showed that the average test score was quite low, amounting to 49.77. After counseling, the post-test results showed a fairly high increase with an average score of 91.14. This increase shows that the management's knowledge has increased from the previous one. The service activity was also accompanied by the handing over of personal protective equipment for administrators in the form of face shields, masks, hand sanitizers, hand washing soap, plastic gloves and hand washing vats. It is hoped that the covid19 transmission chain can be broken and e-Warong administrators can do their job well and smoothly.